Sustained Ventricular Tachycardia in Acute Coronary Syndrome with ST Segment Elevation: Incidence, Predictive Factors and Related Mortality. - ZOUZOU, Hanane (Clinical Medicine And Health Research Journal, 2023)
Background: Sustained Ventricular Tachycardia is the most serious complication; in acute coronary syndrome with ST segment elevation, several international studies have reported incidence and predictive factors of severe ventricular arrhythmias, without identifying sustained ventricular tachycardia separately; also, its epidemiological data is lacking in Algeria. Aims: The main objective of our study is the determination of the frequency of sustained ventricular tachycardia in acute coronary syndrome with ST segment elevation, the secondary objective was the analysis of predictive factors of this arrhythmia, and related mortality. Methods and materials: In this prospective study, conducted in the cardiology department of Hussein Dey hospital (Algiers-Algeria), 467 patients with acute coronary syndrome with elevated ST segment (87 women and 380 men) were enrolled between 28 February 2014 and 16 July 2015. The average age is 60 ± 13 years; at admission, a Holter recorder was attached for continuous ECG monitoring during 48 hours Kruskal’s ANNOVA or H tests were used for comparison of quantitative variables, χ2 test or Fisher’s exact test, were used for qualitative variables, all tests were performed with 1st species risk of 5%. Results: The frequency of Sustained Ventricular Tachycardia is 3.6 % (17 patients), CI 95%: [1.9%-5.3%], multivariate analysis identified the following independent predictors: low diastolic blood pressure, severe coronary artery lesions, Elevated high sensitive troponin concentrations more than 5ng/ml. The risk of mortality expressed by Hazard Ration (HR) is 6. (CI95%: [1.7-21], p = 0.005); the predictors of mortality are: occurrence of ventricular fibrillation and low diastolic blood pressure. Conclusion: Sustained Ventricular tachycardia is the most serious complication during acute coronary syndrome with elevated ST segment, its predictive factors according to our study are: low diastolic blood pressure, severe coronary lesions, Elevated high sensitive troponin concentrations more than 5ng/ml, its occurrence increases the risk of hospital mortality.